Zero-emission of palm oil mill effluent final discharge promoted bacterial biodiversity rebound in the receiving water system - Mohamad-Zainal, Noor Shaidatul Lyana; Ramli, Norhayati; Zolkefli, Nurhasliza; Jamari, Nur Azyani (MDPI AG, 2021)
Zero-emission technology for palm oil mill effluent (POME) has led to a breakthrough in the palm oil industry in relation to the goal of sustainable development. However, there are limited resources on how this technology has affected the bacterial community in the receiving river that has previously been polluted with POME final discharge. Thus, the current study assessed the recoverability of the unexplored bacterial community in the receiving water of a constructed river water system post-zero emission of POME final discharge. An artificial river water system was constructed in this study, where the viability status and the composition of the bacterial community were assessed for 15 days using a flow cytometry-based assay and high-throughput sequencing by Illumina MiSeq, respectively. The zero-emission of POME final discharge reduced not only the physicochemical properties and nutrient contents of the receiving water, but also the bacterial cells’ viability from 40.3% to 24.5% and shifted the high nucleic acid (HNA) to low nucleic acid (LNA) content (38.7% to 34.5%). The proposed POME bacterial indicators, Alcaligenaceae and Chromatiaceae were not detectable in the rainwater (control) but were detected in the artificial river water system after the introduction of POME final discharge at the compositions of 1.0–1.3% and 2.2–5.1%, respectively. The implementation of a zero-emission system decreased the composition of Chromatiaceae from 2.2% on day 8 until it was undetectable on day 15, while Alcaligenaceae was continuously reduced from 1.2% to 0.9% within that similar time frame. As indicated by principal coordinate (PCO) analysis, the reductions in biological oxygen demand (BOD5) would further diminish the compositions of these bioindicators. The zero-emission of POME final discharge has demonstrated its efficacy, not only in reducing the polluting properties, but also in the bacterial biodiversity rebound in the affected water system.